Image Improvement Using The Combination of Wavelet and Multiwavelet Transform - B.J. AL-Khafaji (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
This paper introduces method of image enhancement using the combination of both wavelet and Multiwavelet transformation. New technique is proposed for image enhancement using one smoothing filter.